2022
DOI: 10.3389/ftox.2022.840606
|View full text |Cite
|
Sign up to set email alerts
|

A New Immortalized Human Alveolar Epithelial Cell Model to Study Lung Injury and Toxicity on a Breathing Lung-On-Chip System

Abstract: The evaluation of inhalation toxicity, drug safety and efficacy assessment, as well as the investigation of complex disease pathomechanisms, are increasingly relying on in vitro lung models. This is due to the progressive shift towards human-based systems for more predictive and translational research. While several cellular models are currently available for the upper airways, modelling the distal alveolar region poses several constraints that make the standardization of reliable alveolar in vitro models rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 115 publications
0
16
0
Order By: Relevance
“…ALI along with CS culture conditions has a tremendous influence on the alveolar barrier and made it highly sensitive to the exposed NPs and PHMG. From our previous study (Sengupta et al, 2022) we had observed changes with the actin fibers on CS, which might hint towards a cytoskeletal rearrangement which facilitates better sensitivity to the exposed toxicants. Recent studies have shown convincing evidence that cell-ECM interactions play an important role for particle uptake kinetics and subsequent inflammation (Augustine et al, 2020;Engin et al, 2017;A;Lee et al, 2022).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…ALI along with CS culture conditions has a tremendous influence on the alveolar barrier and made it highly sensitive to the exposed NPs and PHMG. From our previous study (Sengupta et al, 2022) we had observed changes with the actin fibers on CS, which might hint towards a cytoskeletal rearrangement which facilitates better sensitivity to the exposed toxicants. Recent studies have shown convincing evidence that cell-ECM interactions play an important role for particle uptake kinetics and subsequent inflammation (Augustine et al, 2020;Engin et al, 2017;A;Lee et al, 2022).…”
Section: Discussionmentioning
confidence: 89%
“…As described previously in Stucki et al, 2018 and Sengupta et al, 2022 , the AX Lung-on-chip system (AlveoliX AG, Switzerland) comprises of the Lung-on-Chip (AX12) consumable along with two electro-pneumatic devices ( AX Exchanger and AX Breather), and the interface platform ( AX Dock) ( Figure 1B ). Cell seeding and medium exchanges were performed as recommended by the manufacturer (AlveoliX AG).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations